Structural elucidation of propargylated products of 3-substituted-1,2,4-triazole-5-thiols by NMR techniques - Chaudhary, Preeti M.; Chavan, Sayalee R.; Kavitha, M.; Maybhate, Shailaja P.; Deshpande, Sunita R.; Likhite, Anjali P.; Rajamohanan, P. R. (Magnetic Resonance in Chemistry, 2008)
Propargylation of 3-substituted-1,2,4-triazole-5-thiols, which predominantly exist as their thione tautomers, was carried out with the view to synthesize different heterocycles and study their biological activity. Three different products namely, a mono S-propargyl and two S,N-dipropargyl regioisomers, arising from N1/N2 substitution, were isolated and characterized. Unambiguous structural elucidation of the regioisomers of S,N-dipropargyl derivatives was achieved by means of (13)C-(1)H HMBC technique. The proportion of the regioisomers was found to vary with the substituent on the 1,2,4-triazole thiols. No product corresponding to N4 substitution was isolated from any of the reactions carried out. Copyright (C) 2008 John Wiley & Sons, Ltd.
Keywords: (1)H NMR; (13)C NMR; (15)N NMR; 1; 2; 4-triazoles; HMBC; NMR; Regioisomers

GIAO/DFT studies on 1,2,4-triazole-5-thiones and their propargyl derivatives - Phalgune, Usha D.; Vanka, Kumar; Rajamohanan, P. R. (Magnetic Resonance in Chemistry, 2013)
Density functional theory (DFT)/Becke-Lee-Yang-Parr (B3LYP) and gauge-including atomic orbital (GIAO) calculations were performed on a number of 1,2,4-triazole derivatives, and the optimized structural parameters were employed to ascertain the nature of their predominant tautomers. C-13 and N-15 NMR chemical shifts of 3-substituted 1,2,4-triazole-5-thiones and their propargylated derivatives were calculated via GIAO/DFT approach at the B3LYP level of theory with geometry optimization using a 6-311++G** basis set. A good agreement between theoretical and experimental C-13 and N-15 NMR chemical shifts could be found for the systems investigated. The data generated were useful in predicting N-15 chemical shifts of all the nitrogen atoms of the triazole ring, some of which could not be obtained in solution state N-15 HMBC/HSQC NMR measurements. The energy profile computed for the dipropargylated derivatives was found to follow the product distribution profile of regioisomers formed during propargylation of 1,2,4-triazole thiones. Copyright (c) 2013 John Wiley & Sons, Ltd.
Keywords: 1; 2; 4-triazole-5-thiones; C-13; DFT; GIAO; N-15; NMR; Regioisomers; tautomers

Highly regioselective C4-hydrazinylation of 2,4-dichloroquinolines: expedient synthesis of aminoquinoline substituted pyrrolidin-2,5-diones via hydrazinylquinolines - Kumar, Gopal Senthil; Zeller, Matthias; Gonnade, Rajesh Ghanshyam; Prasad, Kamam Jayarampillai Rajendra (Tetrahedron Letters, 2014)
A new class of hydrazinylquinoline regio-isomers has been synthesized through SNAr reaction of 2,4-dichloroquinolines with hydrazine hydrate. The reaction stops at the mono-substitution product with high regioselectivity at the C-4 rather than C-2 position of dichloroquinolines. The hydrazinylquinolines were subsequently converted into aminoquinoline substituted pyrrolidin-2,5-diones in the presence of Eaton's reagent. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: 5-diones; Eaton's reagent; Hydrazinylquinolines; Pyrrolidin-2; Regioisomers; SNAr reaction